Advanced liver function assessment in patients with intestinal failure on long-term parenteral nutrition. Issue 2 (February 2020) - Blüthner, Elisabeth; Bednarsch, Jan; Pape, Ulrich-Frank; Karber, Mirjam; Maasberg, Sebastian; Gerlach, Undine A.; Pascher, Andreas; Wiedenmann, Bertram; Pratschke, Johann; Stockmann, Martin
Summary: Background & aims: Intestinal failure associated liver disease (IFALD) is one of the leading complications and causes of deaths in adult patients receiving home parenteral nutrition for chronic intestinal failure (CIF). Early diagnosis of IFALD is key to alleviate the progression of hepatic dysfunction. The aim of this study was to evaluate the capability of noninvasive liver function tests. Methods: 90 adult patients with CIF receiving long-term home parenteral nutrition were included in a prospective cross-sectional study at our department between 2014 and 2017. All participants underwent dynamic liver function assessment (maximum liver function capacity [LiMAx] test, indocyanine green [ICG] test), transient elastography (FibroScan), blood tests and comprehensive nutritional status assessment. Univariate and multivariable analysis were performed to identify predictors of liver function. Results: LiMAx, ICG test, and FibroScan highly correlated with standard liver function tests. Multivariable analysis identified intact ileum (B = 520.895; p = 0.010), digestive anatomy type 3 (B = 75.612; p = 0.025), citrulline level (B = 3.428; p = 0.040), parenteral olive oil intake (B = −0.570; p = 0.043), and oral intake (B = 182.227; p = 0.040) as independent risk factors affecting liver function determined by LiMAx test. ICG test and FibroScan showed no correlation with gastrointestinal and nutrition-related parameters. Conclusion: The LiMAx test is significantly associated with widely accepted risk factors for IFALD by multivariable analysis, whereas ICG test and FibroScan failed to show significant correlations. Liver function assessment by LiMAx test may therefore have the potential to detect alterations in liver function and identify patients at risk for the development of IFALD. Longitudinal studies are needed to investigate the impact of liver function determined by LiMAx test on long-term outcome in patients with CIF.